Prosthodontic rehabilitation: Cutting edge treatment for amelogenesis imperfecta - Saurav Banerjee; Debabrata Biswas (Wolters Kluwer Medknow Publications, 2022)
Amelogenesis imperfecta is a genetically determined inherited disorder characterized by abnormal formation of tooth enamel leading to esthetic, functional, and psychological impact on the patient. If teeth affected are not treated early; the existing condition will further deteriorate, leading to injury to the attachment apparatus complicating the proposed treatment plan and future prognosis. The definitive objectives of this rehabilitation were to eradicate tooth sensitivity while restoring masticatory function and enhancing esthetics. Treatment plan included root canal treatment of the decrepit teeth followed by porcelain fused to metal restoration. This case report highlight the prosthodontic management of a patient diagnosed with hypomaturation type amelogenesis imperfecta.